Textual and extra-textual elements in Yu Guangzhong’s self-translated poetry into English - Li, Shengnan (2024)
Yu Guangzhong, a distinguished Chinese literary scholar, poet and translator, is a shining figure in the practice of self-translation, masterfully rendering Chinese poetry into English. This study focuses on Yu Guangzhong’s self-translated poetry collection The Night Watchman, examines his self-translation strategies and proposes a practical prototype model based on these strategies. The aim is to offer a framework and methodology for poetry self-translation and literary translation. This study draws on the theoretical framework of Dastjerdi et al. (2008) and Lefevere’s (1975) theory of translation strategies in poetry. Dastjerdi et al. (2008) presents a framework that analyses Yu Guangzhong’s poetry based on textual elements, including form, sound, image, word, tone, content and extra-textual elements such as culture-specific words. Lefevere’s (1975) theory outlines seven strategies for translating poetry. The integration of these two theoretical frameworks enables an analysis of the translation strategies employed by Yu Guangzhong to reproduce textual and extra-textual elements from the original poems in the translated texts, thereby achieving logical and emotional appeal and coherence. This study selects 11 poems from Yu Guangzhong’s poetry collection The Night Watchman, which are presented both in the original language and in English. These poems cover the major themes of his poetic genres, including nostalgia, love, self-reflection, social issues, time, seasons and nature. The selected works represent Yu Guangzhong’s distinctive style and allow for a broader analysis of his self-translation strategies. This selection is in line with the criteria for qualitative textual analysis and ensures that each selected poem serves as a significant case study of Yu Guangzhong’s self-translation strategies. The findings show that Yu Guangzhong employs five translation strategies: metrical translation, literal translation, blank verse translation and interpretation strategy. Yu Guangzhong employs diverse translation strategies on the textual and extra-textual level. On the form level, he often uses metrical and literal translation to maintain the form and structure of the original poem. On the tonal and extra-textual level, he often employs metrical and blank verse translations so that the translation reflects the original poem and at the same time takes into account the readability and comprehensibility of the translated text. The study presents a prototype model of self-translation and offers theoretical guidance for poets and self-translators in the translation of poetry. This model analyses and clarifies Yu Guangzhong’s self-translation strategies on both the textual and extra-textual levels, and also addresses the specific challenges faced by self-translators of poetry, especially when translating rhymes from Chinese poetry into English poetry, thus contributing to translation studies. Future research may investigate further self-translations of Yu Guangzhong’s poems to extend the current model of self-translation. This study may also explore the translation strategies adopted by self-translators from different countries to facilitate the global application of the model of self-translation.